(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2014)
The dependence of spectral properties and interfragmental charge transfer (ICT) on excitation, relaxation and excited state deactivation of 2-(3-coumaroyl)-benzopyrylium perchlorates has been analyzed. It was found that the positions of emission bands and rate constants of radiationless deactivation linearly correlate with ICT upon excited state deactivation, and Stokes’ shifts of fluorescence demonstrate linear dependence on ICT upon structural relaxation in the excited state.